Carpal tunnel syndrome symptoms and their associated factors among plastic surgeons in Saudi Arabia: a cross-sectional study - Ahmed Alharbi; Kayan Alotaibi; Alya AlZabin; Ebtesam Almajed; Ghaida Alotaibi; Norah Alqntash; Haya Alotaibi (BMC Musculoskeletal Disorders)
Abstract Background Carpal tunnel syndrome (CTS) is a common occupational risk for plastic surgeons, affecting hand functionality and overall quality of life. This study aimed to explore and determine CTS symptoms prevalence and risk factors among plastic surgeons in Saudi Arabia. Methods This cross-sectional study utilized an online questionnaire to poll plastic surgeons in Saudi Arabia. Participants submitted sociodemographic data, clinical attributes, and completed the Boston Carpal Tunnel Syndrome Questionnaire (BCTQ). The data were examined via descriptive statistics, bivariate correlation, and multivariable regression analysis. Results Among the 100 surveyed surgeons, the prevalence of CTS symptoms was significant, with 43% indicating hand numbness. Key predictors of CTS symptoms comprised years of experience, a history of degenerative disc disease, and hand numbness. Predictors of increased CTS-associated functional status included surgeons with numbness in both dominant and non-dominant hands, and increased frequency of performing liposuction procedures. Conclusion The occupational hazard of CTS among plastic surgeons in Saudi Arabia is significant, indicating the necessity for focused interventions to reduce CTS risk factors and enhance ergonomic procedures in surgical environments.